Simulation of the COVID-19 handling policy in Indonesia - Erman Aminullah; Erwiza Erman; Tri Edhi Budhi Soesilo (AOSIS, 2023)
Background. This study's background was inspired by the current COVID-19 handling policy, which focuses on the balance of public health and social economy. However, there is a knowledge gap on the dynamic complexity of balancing public health and social economy during the new normal period of COVID-19 handling policy. A system dynamics simulation of the COVID-19 handling policy could be used to understand that gap. Objective. This study aims to uncover the simulation of the COVID-19 handling policy in Indonesia. Methods. This study combined quantitative and qualitative modeling methods with a system dynamics tool. Results. This study revealed 3 elements in the dynamic balance of public health and social economy in the COVID handling policy system: i) COVID-19 and social-economic control; ii) COVID-19 escalation and de-escalation; iii) people's immunity enhancement. Such a mix of COVID-19-controlling policy instruments has maintained a dynamic equilibrium between easing economic suppression at the expense of worsening COVID-19 and tightening public health resolution at the expense of more economic suppression. Conclusions. The study conclusions are as follows: i) the COVID-19 handling policy worked as a leverage factor in balancing public health resolution and economic interest during the new normal period in Indonesia; ii) experiential creativity to respond to the newly serious public health problems triggered by COVID-19 implies adding public health knowledge; iii) the study's outcomes imply re-examining the strengths and deficiencies of the entire health system for a better health system.